A systematic review of the mental health changes of children and young people before and during the COVID-19 pandemic - Kauhanen Laura; Wan Mohd Yunus Wan Mohd Azam; Lempinen Lotta; Peltonen Kirsi; Gyllenberg David; Mishina Kaisa; Gilbert Sonja; Bastola Kalpana; Brown June SL; Sourander Andre (SPRINGER, 2022)
There is increasing knowledge that the COVID-19 pandemic has had an impact on mental health of children and young people. However, the global evidence of mental health changes before compared to during the COVID-19 pandemic focusing on children and young people has not been systematically reviewed. This systematic review examined longitudinal and repeated cross-sectional studies comparing before and during COVID-19 pandemic data to determine whether the mental health of children and young people had changed before and during the COVID-19 pandemic. The Web of Science, PubMed, Embase and PsycINFO databases were searched to identify peer-reviewed studies that had been published in English and focused on children and young people between 0 and 24 years of age. This identified 21 studies from 11 countries, covering more than 96,000 subjects from 3 to 24 years of age. Pre-pandemic and pandemic data were compared. Most studies reported longitudinal deterioration in the mental health of adolescents and young people, with increased depression, anxiety and psychological distress after the pandemic started. Other findings included deteriorated negative affect, mental well-being and increased loneliness. Comparing data for pandemic and pre-pandemic periods showed that the COVID-19 pandemic may negatively impact the mental health of children and young people. There is an urgent need for high-quality research to address the impact, risks and protective factors of the pandemic on their mental health, as this will provide a good foundation for dealing with future health emergencies and other crises.